Do mother's education and foreign born status interact to influence birth outcomes? Clarifying the epidemiological paradox and the healthy migrant effect. Issue 5 (15th April 2008) - Auger, N; Luo, Z-C; Platt, R W; Daniel, M
Abstract : Introduction: The unresolved "epidemiological paradox" concerns the association between low socioeconomic status and unexpectedly favourable birth outcomes in foreign born mothers. The "healthy migrant" effect concerns the association between foreign born status per se and birth outcomes. The epidemiological paradox and healthy migrant effect were analysed for newborns in a favourable sociopolitical environment. Methods: 98 330 live births to mothers in Montreal, Canada from 1997 to 2001 were analysed. Mothers were categorised as foreign born versus Canadian born. Outcomes were: small for gestational age (SGA) birth; low birth weight (LBW) and preterm birth (PTB). Multilevel logistic regression was used to examine the interaction between maternal education and foreign born status, adjusting for covariates. Results: Not having a high school diploma was associated with LBW in Canadian (odds ratio (OR) 3.20; 95% CI 2.61 to 3.91) but not foreign born (OR 1.14; 95% CI 0.99 to 2.10) mothers and was more strongly associated with SGA birth in Canadian (OR 2.03; 95% CI 1.84 to 2.22) than in foreign born (OR 1.26; 95% CI 1.07 to 1.49) mothers. Foreign born status was associated with SGA birth (OR 1.37; 95% CI 1.28 to 1.47), LBW (OR 1.51; 95% CI 1.27 to 1.79) and PTB (OR 1.12; 95% CI 1.03 to 1.22) in university-educated mothers only. Conclusions: The epidemiological paradox associated with low educational attainment was present for SGA birth and LBW but not PTB. Foreign born status was associated with adverse birth outcomes in university-educated mothers, the opposite of the healthy migrant effect.